Is the woman in the Song of Songs really that free? 1 - Ndoga, S. S. (Hervormde teologiese studies, 2000)
The Song of Songs has often been treated as a platform for feminist liberationist causes. This study aims to re-examine some feminist ideological readings of the Song of Songs. Although feminist scholars insist thal the female "voice" is very conspicuous in the Song, the male voice is also constantly ''there'' and equally strong. Thus, the Song does not celebrate the supremacy of either gender, but praises mutuality and equality. As analysis of a sample text, 1:2-4, is carried out, using a "newcomer" approach (at least to Old Testament studies), namely socio-rhetorical criticism. This approach allows an integrated scientific approach to the reading and rereading of texts from various angles. Ideological questions come into focus, such as: What exactly does an ideology involve or imply? Whose ideological reading is the best reading of the text? Is there such a thing as a best reading of a text? Does the Song of Songs itself prescribe a particular ideological reading? Finally, applications and principles as derived from the exegetical findings are summarised to encourage a wider readership and use for the Song of Songs.